The Role of TikTok (Douyin) in Shaping Private and Public Spheres and Youth Political Voice - Lu, Manxi (International Journal of Social Sciences and Public Administration, 2024)
This article examines the impact of TikTok (known as Douyin in China) on the relationship between the private and public spheres in the digital era. Drawing on Habermas's public sphere theory and other relevant academic perspectives, it argues that while Douyin has redefined the interaction between the private and public spheres by enabling users to share private lives publicly and blurring the boundaries, there are significant limitations when it comes to its suitability as an ideal public sphere for young people to voice political views in China. The platform's entertainment content, recommendation algorithm, strict censorship, and emotional nature of discussions lead to fragmented, superficial, and restricted political conversations. Although young people find creative ways to express political ideas, real in-depth and diverse political discussions are hindered. Overall, Douyin has blurred the boundaries between the private and public spheres to an extent but has many constraints as a platform for political discussion.